Functional characterization of high-yield plant protein powder valorized from de-oiled sour cherry seed using microwave-assisted enzymatic extraction followed by spray- and freeze-drying - Başyiğit, Bülent; Görgüç, Ahmet; Gençdağ, Esra; Cansu, Ümran; Yılmaz, Fatih Mehmet; Karaaslan, Mehmet (Biomass conversion and biorefinery, 2023)
The pits of sour (tart) cherry have been recently exploited as a rich source of protein. The objective of this study was to produce protein powders from the “waste of by-product” left after the separation of precious oils from the kernel. In this context, microwave-assisted enzymatic extraction was primarily carried out after determining the appropriate enzyme, then protein powders were successfully produced. The effectiveness of process parameters were investigated, and optimum conditions were determined for both extraction and spray-drying steps using response surface methodology (RSM). The highest protein isolation rate (94.5%) was achieved with the process conditions of 0.12 AU/100 g alcalase concentration, 10.9 pH value, 48 °C, and 13 min of microwave-assisted extraction. Plausible spray-drying conditions were 188 °C for air inlet temperature and 24% for feed rate with the responses of 55.23% powder yield and 0.27 water activity value. The protein contents of final hydrolysates were 80.56% for spray-drying and 79.22% for freeze-drying. Cell culture studies were conducted to demonstrate cytotoxic and anti-cancerogenic behavior of protein powders. Spray-drying significantly improved emulsion activity and stability, oil binding, and foaming capacity of powders, while freeze-drying related to better wettability. Both drying methods revealed similar and promising protein solubility values at 2.0–4.0 and 8.0–12.0 pH values. Scanning electron microscope images, Fourier transform infrared spectroscopy, X-ray diffraction spectroscopy, and thermogravimetric analyses were performed to visualize the microstructures and to determine their authenticity and thermal properties. Graphical abstract